Biofilms as potential reservoirs of antimicrobial resistance in vulnerable settings - Nahum, Yanina; Muhvich, Johnathan; Morones-Ramirez, José Rubén; Casillas-Vega, Nestor G.; Zaman, Muhammad H. (Frontiers in Public Health, 2025)
Antimicrobial resistance is a major global health threat, characterized by the ability of microorganisms to withstand the effects of antimicrobial agents. Biofilms, as unique microbial communities, significantly contribute to this threat. They provide a protective environment for pathogens, facilitate horizontal gene transfer, and create an ideal setting for the persistence and evolution of resistant bacteria. This issue can be particularly important in low-income settings and vulnerable communities, such as formal and informal refugee and migrant camps. These settings usually have limited access to healthcare resources and appropriate treatments, contributing to the selective pressure that promotes the survival and proliferation of resistant bacteria. Thus, biofilms formed in wastewater in these areas can play a critical role in spreading antimicrobial resistance or acting as hidden reservoirs for future outbreaks. While emerging efforts focus on detecting antibiotic resistance genes and planktonic bacteria in wastewater, biofilms may be a source of under-appreciated antimicrobial resistance, creating a significant gap in our understanding of resistance dynamics in wastewater systems. Incorporating biofilm surveillance into wastewater monitoring strategies in vulnerable settings can help develop a more comprehensive understanding of resistance transmission and more effective intervention measures in these settings.